2020
DOI: 10.3389/fpsyt.2020.594115
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the COVID-19 Pandemic on Mental Well-Being and Psychological Distress: Impact Upon a Single Country

Abstract: The COVID-19 pandemic is likely to have affected the psychological well-being and mental health of many people. Data on prevalence rates of mental health problems are needed for mental health service planning. Psychological well-being and prevalence of clinically significant mental distress were measured in a large sample from Wales 11–16 weeks into lockdown and compared to population-based data collected in 2019 before the COVID-19 pandemic. Data were collected using an online survey disseminated across Wales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 56 publications
11
94
1
2
Order By: Relevance
“…In consequence, our sample is biased in that it includes a high portion of participants who reported to have been in psychiatric treatment at least once in their lives and experience a slightly higher level of unspecific psychological distress compared to convenience samples from different nationalities during the corona pandemic [e.g. 42 , 43 ]. These biases restrict the external validity and the generalisability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, our sample is biased in that it includes a high portion of participants who reported to have been in psychiatric treatment at least once in their lives and experience a slightly higher level of unspecific psychological distress compared to convenience samples from different nationalities during the corona pandemic [e.g. 42 , 43 ]. These biases restrict the external validity and the generalisability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends were observed in children and adolescents with and without mental disorders during the pandemic ( Conti et al, 2020 ; Guessoum et al, 2020 ; Racine et al, 2020 ; Tanir et al, 2020 ; Zhou et al, 2020 ). In general, younger individuals seemed to be more severely affected by the pandemic than older persons, for example, Gray et al (2020) found a 6.5-fold increased probability of severe psychological distress for the youngest age group (16-24 years) in contrast to participants ≥ 75 years in an online-survey with 12,000 participants.…”
Section: Introductionmentioning
confidence: 91%
“…The health emergency we are experiencing due to COVID-19 has strongly influenced not only physical health but also the mental health of the general population as well as collective behavior (Gray et al, 2020 ; Orrù et al, 2020b ; Lenzo et al, 2021 ). The understanding of mental health consequences must consider individual emotional responses associated with the ongoing stressful experience of the COVID-19 pandemic (Di Giuseppe et al, 2020a ; Venuleo et al, 2020 ).…”
Section: The Psychodynamic Approach Against Covid-related Psychological Consequencesmentioning
confidence: 99%